The Triple Burden Phenomenon and Eating Behaviors of Generation Z: A Phenomenological Study Among Health Science Students - Lutfiah Ramadhani; Nadya Ulfa Tanjung (Karya Kesehatan Siwalima, 2025)
The digital revolution has reshaped the consumption patterns of Generation Z and contributed to the triple burden of malnutrition, including overeating, which has become a growing concern among university students. This study examines the triple burden phenomenon in relation to the eating behaviors of Generation Z at the Faculty of Public Health, State Islamic University of North Sumatra. This qualitative phenomenological research involved 10 students. Data were collected through in-depth interviews and observations, triangulated using a 3×24-hour food recall, and analyzed using the Miles and Huberman model. Calorie requirement calculations based on Body Mass Index (BMI) criteria showed that seven participants exceeded their daily caloric needs, consuming an average of 2,102 calories per day—above the normal requirement. Social media food simulacra triggered visual cravings in eight participants, while mukbang content increased appetite by two to three times. Seven participants demonstrated low self-efficacy in controlling portion sizes. Eating patterns shifted from conventional meal structures to a grazing pattern (6–8 times per day), with fifty-eight percent of eating episodes consisting of snacking, indicating overnutrition within the triple burden context. Social media simulacra and low self-efficacy significantly influenced overeating among Generation Z, even among individuals with adequate nutritional knowledge. Social media creates a hyperreality that encourages consumption beyond biological needs, contributing to the complexity of the triple burden of malnutrition in the digital era. Strengthening digital literacy and self-efficacy is recommended to address the triple burden among Generation Z